Methyl Ester-Mineral Oil Mixture under Thermal Aging - Rajab, Abdul; Alfaradhi, Panglima Ibnu; Putra, Rizky Kencana; Nofendra, Riko (Jurusan Teknik Elektro Universitas Andalas, 2023)
Replacement with natural esters (retrofilling) is an alternative solution to extend the life expectancy of an oil-filled transformer containing mineral oil. During the retro-filling process, some portions of the mineral oil remain inside the transformer's tank, forming a mixture between the used mineral oil and the new vegetable oil. In this investigation, methyl ester was mixed with a relatively low percentage of mineral oil to simulate the retro-filling process. The aim is to examine the characteristics of a mixture of mineral and vegetable oils under thermal aging. Thermal aging treatments were carried out at 120°C for 28 days and 140°C for 14 days. Kraft paper and copper wire were incorporated during the aging test. After thermal aging, the characteristics of the oil mixture were evaluated based on electrical, physical, and chemical characteristics. The result shows that physical and chemical characteristics are significantly influenced by the increase in mineral oil content and the temperature of thermal aging. However, the breakdown voltage increased after thermal aging, but at a higher temperature, the breakdown voltage dropped as the mineral oil content increased.